Slower Calcium Handling Balances Faster Cross-Bridge Cycling in Human MYBPC3 HCM. Issue 5 (6th February 2023) - Pioner, Josè Manuel; Vitale, Giulia; Steczina, Sonette; Langione, Marianna; Margara, Francesca; Santini, Lorenzo; Giardini, Francesco; Lazzeri, Erica; Piroddi, Nicoletta; Scellini, Beatrice; Palandri, Chiara; Schuldt, Maike; et al.
Abstract : Background: The pathogenesis of MYBPC3 -associated hypertrophic cardiomyopathy (HCM) is still unresolved. In our HCM patient cohort, a large and well-characterized population carrying the MYBPC3 :c772G>A variant (p.Glu258Lys, E258K) provides the unique opportunity to study the basic mechanisms of MYBPC3 -HCM with a comprehensive translational approach. Methods: We collected clinical and genetic data from 93 HCM patients carrying the MYBPC3 :c772G>A variant. Functional perturbations were investigated using different biophysical techniques in left ventricular samples from 4 patients who underwent myectomy for refractory outflow obstruction, compared with samples from non-failing non-hypertrophic surgical patients and healthy donors. Human induced pluripotent stem cell (hiPSC)-derived cardiomyocytes and engineered heart tissues (EHTs) were also investigated. Results: Haplotype analysis revealed MYBPC3 :c772G>A as a founder mutation in Tuscany. In ventricular myocardium, the mutation leads to reduced cMyBP-C (cardiac myosin binding protein-C) expression, supporting haploinsufficiency as the main primary disease mechanism. Mechanical studies in single myofibrils and permeabilized muscle strips highlighted faster cross-bridge cycling, and higher energy cost of tension generation. A novel approach based on tissue clearing and advanced optical microscopy supported the idea that the sarcomere energetics dysfunction is intrinsically related with the reduction in cMyBP-C. Studies in single cardiomyocytes (native and hiPSC-derived), intact trabeculae and hiPSC-EHTs revealed prolonged action potentials, slower Ca 2+ transients and preserved twitch duration, suggesting that the slower excitation-contraction coupling counterbalanced the faster sarcomere kinetics. This conclusion was strengthened by in silico simulations. Conclusions: HCM-related MYBPC3 :c772G>A mutation invariably impairs sarcomere energetics and cross-bridge cycling. Compensatory electrophysiological changes (eg, reduced potassium channel expression) appear to preserve twitch contraction parameters, but may expose patients to greater arrhythmic propensity and disease progression. Therapeutic approaches correcting the primary sarcomeric defects may prevent secondary cardiomyocyte remodeling.